Age-stratified assessment of orthodontic tooth movement outcomes with clear aligners - Mariamma Chaluparambil; Sarah Abu Arqub; Chia-Ling Kuo; Lucas Da Cunha Godoy; Madhur Upadhyay; Sumit Yadav (SpringerOpen, 2024)
Abstract Objective This study compared the achieved tooth movement to that predicted in the preliminary simulated digital treatment plan between adults and teenagers. Materials and methods Records of 60 patients (30 adults; mean age: 36.6 ± 11.36 years, and 30 teenagers; mean age: 16.23 ± 2.25 years) were randomly selected. Initial and predicted models were obtained from the initial simulated treatment plan. The first model of the refinement scan was labeled as achieved. SlicerCMF software (version 3.1; https://www.slicer.org ) was used to superimpose the achieved and predicted digital models over the initial ones with regional superimposition on relatively stable first molars. 600 teeth were measured in each group for horizontal, vertical, angular movements, and transverse dimensions. Accuracy was defined as the achieved amount of movement minus predicted and was calculated for each individual and compared between teens and adults. Results The mandibular inter-canine width accuracy was statistically significant between groups (p = 0.050). Significant under-correction in horizontal movements was noted for mandibular first premolars in teenagers compared to adults (p = 0.037). There was considerable over-correction in horizontal movements for mandibular central and lateral incisors between groups (p < 0.05). No significant difference was observed between groups in the vertical plane. Rotations were underachieved for maxillary first premolars, more in adults than teenagers (p = 0.017). Conclusion The accuracy of achieved versus predicted tooth movement between adults and teenagers was significant for the inter-canine width. Mandibular central and lateral incisors showed significantly greater over-correction in adults in the horizontal plane. The accuracy of rotations and vertical movements was comparable.